Implementation of ESG in Blue Ocean Strategy: A Case Study of PT Wijaya Karya (Persero) Tbk - Zhavira, Nakita Al; Ratnawati, Anny; Shalihati, Fithriyyah (Business Review and Case Studies, 2025)
Background: The construction industry contributes significantly to Indonesia’s economy, but the Covid-19 pandemic is causing difficulties for the sector. PT Wijaya Karya (WIKA), identified the need to diversify its products and services to cope with the decline in market size and maintain revenue stability. WIKA has the opportunity to apply Environmental, Social, and Governance (ESG) principles which have been implemented albeit unconsciously or sporadically. Purpose: This research aims to recommend ESG implementation strategies to create a blue ocean market towards sustainability. Design/methodology/approach: This research uses a qualitative method with descriptive data analysis and strategy formulation through the blue ocean strategy approach, utilizing the strategy canvas and four-action framework. Primary data was collected through in-depth interviews and questionnaires with senior management and division employees, while secondary data came from company reports and literature reviews. Findings/results: The results showed that the strategy canvas identified 10 main ESG initiatives with varying performance, helping WIKA map out strengths and areas that need to be optimized. The 10 initiatives are Products Sustainability, Energy Efficiency, Hazardous Waste Management, Greenhouse Gas Emission Reduction, Environmental Conservation, Social and Environmental Responsibility, Occupational Health and Safety, Respectful Workplace, The Implementation of Anti-bribery Management System, and Risk Governance. Conclusion: Strategy recommendations include Resource Optimization to improve resource allocation and more optimal productivity, Competency and Awareness Improvement to ensure employees have the necessary skills and understand the benefits of ESG, and Market Strengthening and Transparency to increase market awareness and demand, as well as transparency and accountability. The implementation of this strategy is expected to strengthen ESG as part of WIKA’s strategy, creating strong sustainable value towards a more stable and profitable market. Originality/value (state of the art): This research highlights the importance of integrating ESG principles with the Blue Ocean Strategy to create innovative and sustainable business strategies in the construction sector, ultimately supporting market growth and company stability. Keywords: blue ocean strategy, construction, ESG, strategic innovation, sustainability